Sintering of MAX-phase materials by spark plasma and other methods - Lyu, J.; Kashkarov, E. B.; Travitzky, Nahum; Syrtanov, M. S.; Lider, A. M. (Journal of Materials Science, 2020)
This review focuses on the comparison of the spark plasma sintering (SPS) with other fabrication methods of MAX-phase materials. In the view of optimizing properties for prospective applications, we summarized different routes to synthesize and sinter bulk/powder MAX-phases with various microstructures, discussed the phase composition of MAX-phases obtained by SPS and other methods. In the article, we introduced the experimental features of various sintering methods and carried out the comparative analysis of “competition phenomenon” between the SPSed MAX-phases and MAX-phases prepared by other technologies. We referred to relevant reports and reviews in which one can acquire a comprehensive understanding of sintering kinetics, sintering thermodynamics, grain growth kinetics, and densification mechanisms. Furthermore, the influence of the sintering routes on the properties of the MAX-phases was discussed paying emphasis on the mechanical properties.
CRIS-Team Scopus Importer:2020-10-09